Influence des pressions anthropiques sur la structure des populations de Pentadesma butyracea au Bénin - Aliou Dicko; Samadori Sorotori Honoré Biaou; Armand Kuyema Natta; Choukouratou Aboudou Salami Gado; M’Mouyohoum Kouagou (VertigO)
The present study examined the influence of human activities on the structural characteristics of the populations of P. butyracea, a vulnerable multipurpose woody species. A total of 116 plots of 500 m² were randomly installed, 68 in the sudanian region and 48 in the sudano-guinean region, for dendrometric and floristic inventories. The populations of P. butyracea were categorized according to human pressures they are exposed to, using a Factorial Analysis of Correspondences. Three groups were discriminated : Group 1 (populations of Penessoulou and Kandi), characterized by a pressure from wild vegetation fires and agricultural activities ; Group 2 (populations of Manigri and Ségbana), characterized by illegal selective logging, abusive barking of P. butyracea, animal grazing ; and Group 3 (populations of Natitingou, Toucountouna and Tchaourou), characterized by excessive seeds collection and sand removal from the stream by humans. The diameter distribution structures were of left or right dissymmetry according to pressures types to which the discriminated groups are subjected. For a conservation of remnant populations of P. butyracea, the most degraded gallery forest stands should be reforested while protecting the least degraded ones.